Th1 responses in vivo require cell-specific provision of OX40L dictated byenvironmental cues - Gerard, A (Springer Nature, 2020)
The OX40-OX40L pathway provides crucial co-stimulatory signals for CD4 T cell responses, however the precise cellular interactions critical for OX40L provision in vivo and when these occur, remains unclear. Here, we demonstrate that provision of OX40L by dendritic cells (DCs), but not T cells, B cells nor group 3 innate lymphoid cells (ILC3s), is critical specifically for the effector Th1 response to an acute systemic infection with Listeria monocytogenes (Lm). OX40L expression by DCs is regulated by cross-talk with NK cells, with IFNγ signalling to the DC to enhance OX40L in a mechanism conserved in both mouse and human DCs. Strikingly, DC expression of OX40L is redundant in a chronic intestinal Th1 response and expression by ILC3s is necessary. Collectively these data reveal tissue specific compartmentalisation of the cellular provision of OX40L and define a mechanism controlling DC expression of OX40L in vivo.